Comparisons Of Magnet Retained Sectional Obturator And Single Piece Obturator - Aida Ali; Zakiah Isa (Universtas Sumatera Utara, 2024)
Oranasal separation and the rehabilitation of oral functions are the main objectives of providing obturators for patient with maxillary defects. This study compared patient satisfaction with a single-piece and a magnet-retained sectional obturator. Seven patient with maxillary defects were treated with both types of prosthesis. A satisfaction survey was completed after each type of obturator had been worn for at least two months without any complaints. Patient satisfaction regarding their masticatory and speech abilities, aesthetics, prosthesis retention and ease of handling, and the patients’ overall satisfaction with the obturators were measured on a visual analogue scale (VAS) and a 4-scale category (FSC) questionnaire. Statistical analysis of data was conducted using the non-parametric Wilcoxon Signed Ranks test. The results show that the only significant difference in patient satisfaction was the patients’ perception that the sectional obturator provided better aesthetics (p<0.05). It can be concluded that the patients had no preference for a particular type of prosthesis, and that there were satisfied as long as the obturators were comfortable, restored their oral functions and improved their quality of life.